2016
DOI: 10.1177/2333794x16651512
|View full text |Cite
|
Sign up to set email alerts
|

Study of 9 Cases of Tuberculosis Pneumonia in Children at Chu of Brazzaville, Congo

Abstract: In the Republic of Congo, a country where tuberculosis is endemic, there have not been many reports about tuberculosis pneumonia. This study aimed to describe the epidemiology, clinical features, and outcome of tuberculosis pneumonia in children. This was a retrospective study of 9 cases of children admitted from 2002 to 2015, that is, 0.7 cases per year. The average age was 37 months. The mean delay from the beginning of symptoms to the visit to a medical center was 36 days (range = 4-93 days). Physical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…[12] Other studies done in Uganda and Congo showed contrary results where they found that TB is more likely to occur in children under two years of age. [6,13] HIV positive children were 24 times more likely to develop PTB compared to their counterparts who were HIV negative. HIV destroys CD4+ cell and T cell mediated immunity which is critical in fighting against TB bacilli.…”
Section: Factors Associated With Ptb In Children Presenting With Seve...mentioning
confidence: 95%
“…[12] Other studies done in Uganda and Congo showed contrary results where they found that TB is more likely to occur in children under two years of age. [6,13] HIV positive children were 24 times more likely to develop PTB compared to their counterparts who were HIV negative. HIV destroys CD4+ cell and T cell mediated immunity which is critical in fighting against TB bacilli.…”
Section: Factors Associated With Ptb In Children Presenting With Seve...mentioning
confidence: 95%
“…Second, Africa accounts for 29% of global tuberculosis cases [15] that cause pneumonia [16]. Even worse, its symptoms are typical of other bacterial pneumonia, which leads to inadequate treatment [17].…”
Section: Open Accessmentioning
confidence: 99%
“…6 Kolonisasi bakteri patogen adalah tanda penurunan fungsi sistem imun yang tidak mampu membersihkan patogen yang terhirup. 9 Kasus ini datang dengan gejala akut Riwayat kontak dengan pasien terdiagnosis TB merupakan kriteria yang sangat penting untuk diagnosis TB. Riwayat kontak dengan orang dewasa terdiagnosis TB paru atau memiliki gambaran klinis TB memperkuat kemungkinan diagnosis TB.…”
Section: Diskusiunclassified